Regia ri-mediata e partecipativa: Un caso della Compagnia Deflorian/Tagliarini - Raciti, Viviana V. F. (Mimesis Journal, 2021)
Re-mediated and participated direction: a case study by Compagnia Deflorian Tagliarini is an essay focused on the travelling site-specific performance, Quando non so cosa fare cosa faccio? (2016), based on Antonio Pietrangeli’s film Io la conoscevo bene (1965). The two opening paragraphs present an essential theatrography of the Rome-based company, created in 2009 by Daria Deflorian and Antonio Tagliarini (both performers, authors and directors) and their aesthetic of theatre, between performance and theatre, autobiographical elements and reuse of other artistic objects. In this way, the company’s work is part of a precise scenario, belonging to other Italian companies between late xx and early xxi centuries. The main paragraph analyses the case study, clarifying the relationship between the performance itself and the film as a trace of: the environment (the roman neighborhood “Marconi” where the performance took place is the same location of many scenes from the film); the themes and how they are connected between the fictional history of the film character, Adriana, and the real biography of the performer; moreover, the film-perspective is a way to guide the spectator, his/hers involvement, his/hers glance is a sort of framing guided from the inside of the travelling performance.